Evaluation and Treatment Planning to Maximize Perioral, Submental, and Neck Aesthetics - Ma, Cheng; Parikh, Aniruddha; Lighthall, Jessyka G. (Facial Plastic Surgery, 2025)
Aesthetic rejuvenation of the perioral, submental, and neck regions is a complex topic with multiple different treatment approaches. Aging changes in the skin, muscles, fat and soft tissue, and bones are driven by multiple internal and external factors. To obtain the best cosmetic outcome, a deep understanding of the perioral, submental, and neck region and proper patient evaluation are necessary. Here, we discuss the process of evaluating patients and planning treatment for perioral, submental, and neck rejuvenation.Patients presenting for evaluation of perioral, submental, and neck aging may have multiple aesthetic complaints. The approach to evaluating patients should be comprehensive and consistent. This involves careful history taking and consideration of medical co-morbidities, a thorough evaluation of the skin, tone, dynamic movement, and soft-tissue distribution of each subunit, and individualized pretreatment counseling to discuss risks and set expectations.An individualized plan may consist of either nonsurgical, surgical or a combination of approaches. Nonsurgical approaches excel at addressing aging skin, volume deficits, and overactivation of facial musculature. Surgical approaches address more severe manifestations of skin aging, uneven volume distribution, loss of contour in the jaw and neck, and bony deformities.
Keywords: perioral rejuvenation; neck rejuvenation; facial aging; patient evaluation; treatment planning